Comparison of the upper, middle, and lower vertical facial height between Down syndrome and normal children - Mohammad Ali, Nor Dayana; Hartanto, Rudy; Gartika, Meirina (Padjadjaran Journal of Dentistry, 2012)
Introduction: Down syndrome (DS) is a common genetic disorder also known as Trisomy 21.DS individuals have specific physical dysmorphism especially the face. The most common features and problems associated with Down’s syndrome  are characteristic facial features, cognitive problems, congenital heart disease, hearing problems, short stature, thyroid problems and Alzheimer’s disease. This study aims to determine the differences of the vertical facial height measurement (UFH, MFH and LFH) between DS and regular (R) children. Methods: The study is a Cross-sectional analytical. Subjects are 6-13 years of age, with a total of 20 DS children (10 males; 10 females) of selected Sekolah Luar Biasa-C (SLB- Cs) and 160 R school children (80 males; 80 females) from selected Sekolah Dasar Negeri (SDNs) in Kota Bandung. Subjects selected using the three levels Multi stage cluster sampling. Measurements taken were upper, middle and lower facial height with each measurement taken three times. Data was analysed using the t-test and p-value. Results: UFH in DS males are 5.623, 5.986, 6.352, 6.396, 6.585, 6.747,7.109; MFH 3.325, 3.456, 3.457, 3.646, 3.611, 3.720, 3.716 and LFH are 4.163, 4.283, 4.235, 4.771, 4.850, 4.979, 5.132. UFH in R males are 5.924, 6.029, 6.223, 6.362, 6.476, 6.725, 6.903, 7.366; MFH 3.942, 3.998, 4.103, 4.148, 4.175, 4.247, 4.463, 4.534 and LFH 4.509, 4.658, 4.882, 5.058, 5.167, 5.450, 5.532, 5.606. In DS females UFH are 5.745, 5.912, 5.986, 6.394, 6.339, 6.778; MFH 3.575, 3.704, 3.711, 3.768, 3.749, 3.865 and LFH 4.49, 4.552, 4.646, 4.909, 5.034, 5.039. UFH for R females 6.062, 6.167, 6.243, 6.308, 6.476, 6.515, 6.799, 6.965; MFH 3.700, 3.863, 3.981, 4.084,4.091, 4.116, 4.191, 4.221 and LFH 4.576, 4.702, 3.764, 4.998, 5.156, 5.326, 5.374, 5.552 (in cm). Conclusion: There are significant differences with the MFH and LFH between DS and R children and UFH differences is non significant between these two populations.